Coping with the market: Are there cohort effects for organisations in transition? - Michael Wyrwich; Ina Krause (Journal for East European Management Studies, 2011)
This paper investigates the employment growth of small and medium-sized firms that survived the transformation process of the German Democratic Republic (GDR). We find that firms founded in the later period of the GDR's existence have especially low growth prospects, even 10 years after German reunification. The later phase of the GDR was marked by tightening measures intended to enhance political influence on the planned economy, accompanied by a sharp economic decline. Thus, organizations were more deeply embedded in planning structures that were more rigorous than those present in the first years of the GDR's existence. We argue that these organizations therefore developed less appropriate practices for coping with a market economy than organizations founded in other periods. – – Im vorliegenden Aufsatz untersuchen wir die langfristigen Auswirkungen des Transformationsprozesses auf die betriebliche Beschäftigungsentwicklung in klein- und mittelständischen Betrieben in Ostdeutschland. Dabei ist festzustellen, dass einige DDR-Altbetriebe auch über zehn Jahre nach der Wiedervereinigung relativ ungünstige Wachstumsaussichten haben. Die Spätphase der DDR zeichnete sich insbesondere durch die zentrale Lenkung aller wirtschaftlichen Aktivitäten im Sinne einer sozialistischen Planwirtschaft aus. Entsprechend haben DDR-Altbetriebe, die in der Spätphase der DDR gegründet wurden und somit strukturell eher an die Kontextbedingungen der planwirtschaftlich organisierten DDR-Ökonomie angepasst waren, besondere Schwierigkeiten betrieblichen Handlungsroutinen zu entwickeln, die unter marktwirtschaftlichen Bedingungen ein effizientes und wachstumsförderndes Wirtschaften ermöglichen.
Keywords: 650; Transition; East Germany; organizational learning; employment growth